2018
DOI: 10.1016/j.ehj.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

XANTUS-EL: A real-world, prospective, observational study of patients treated with rivaroxaban for stroke prevention in atrial fibrillation in Eastern Europe, Middle East, Africa and Latin America

Abstract: BackgroundThe prospective, observational XANTUS study demonstrated low rates of stroke and major bleeding in real-world rivaroxaban-treated patients with non-valvular atrial fibrillation (NVAF) from Western Europe, Canada and Israel. XANTUS-EL is a component of the overall XANTUS programme and enrolled patients with NVAF treated with rivaroxaban from Eastern Europe, the Middle East and Africa (EEMEA) and Latin America.MethodsPatients with NVAF starting rivaroxaban for stroke prevention were consecutively recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
2
13
0
1
Order By: Relevance
“…Several large real-world evidence studies have been performed to study the safety of the non-vitamin K antagonist oral anticoagulants (NOACs) for stroke prevention in unselected patients with atrial fibrillation (AF). These studies confirm that use of NOACs in routine clinical practice is safe and efficacious, but also show that their reduced doses are far more often prescribed than in the randomised controlled trials (RCTs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These and other phase IV studies on the use of NOACs in patients with AF show important differences among geographical regions regarding patient characteristics and prescription patterns [1,[5][6][7][8][9][10][12][13][14].…”
Section: Introductionsupporting
confidence: 60%
“…Several large real-world evidence studies have been performed to study the safety of the non-vitamin K antagonist oral anticoagulants (NOACs) for stroke prevention in unselected patients with atrial fibrillation (AF). These studies confirm that use of NOACs in routine clinical practice is safe and efficacious, but also show that their reduced doses are far more often prescribed than in the randomised controlled trials (RCTs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These and other phase IV studies on the use of NOACs in patients with AF show important differences among geographical regions regarding patient characteristics and prescription patterns [1,[5][6][7][8][9][10][12][13][14].…”
Section: Introductionsupporting
confidence: 60%
“…The model estimations using epidemiological data in Argentina also suggested that apixaban relative to warfarin in AF patients could reduce the disease burden and costs, and improve patients’ survival and quality of life. [ 30 ] In Eastern Europe, the Middle East, Africa and Latin America, XANTUS-EL study confirmed low stroke and bleeding risks in AF patients treated with rivaroxaban [ 31 ] ;however, warfarin was not the reference in this study. To date, there are still no observational studies directly focusing on the effect of NOACs versus warfarin in LatAm patients with AF.…”
Section: Discussionmentioning
confidence: 63%
“…Regarding the prescriptions of antiarrhythmic drugs in our patients, it is relevant that these were directed more towards control of heart rate than to control of heart rhythm, with use of type III antiarrhythmics being observed in 38.57%, propafenone in 4.45%, BB in 50.44% and digoxin in 26.70%. The REMEFA study (The Mexican Registry of Atrial Fibrillation) 13 compared the rate-control strategy vs the rhythm control strategy in 1,201 patients, reporting better control of arrhythmia and lower incidence of cerebrovascular disease in the rhythm control group. If we analyze the rate-control group of that study, we can observe higher prescriptions than in our study of digoxin (69%), type III antiarrhythmics (59.0%) and BB (56.0%).…”
Section: Discussionmentioning
confidence: 99%